Pelaksanaan Juru Pemantau Jentik Bocah (JUMBO) PKL Komunitas Dusun Klenggotan, Piyungan, Bantul, D.I Yogyakarta - Arifudin Suhaili; Elfrida Riyani; Novita Setyo Cahyani; Dea Nuraini Rahmadhani; Fanisa Laras Budiati; Melati Ayuningtyas; Achmad Husein; Haryono Haryono; Herman Santjoko (JPS : Jurnal Pengabdian Serulingmas, 2022)
Piyungan is one of the sub-districts in Bantul Regency. Based on data on the distribution of dengue fever throughout 2021 in the Piyungan area, Bantul, there were 28 cases of dengue fever. The details of the distribution of the incidence of DHF are 5 cases in Sitimulyo village, 12 cases in Srimulyo village, and 11 cases in Srimartani village. Recapitulating data from the Piyungan Public Health Center, it was concluded that Klenggotan Hamlet, Srimulyo had the most frequent incidence of dengue fever, which was 8 times throughout 2021. Our community PKL activities in January 2022 carried out the activity of forming a juvenile jumantik (JUMBO) in Klenggotan hamlet, Srimulyo, Bantul. The activity of forming JUMBO Klenggotan aims to educate children to care about environmental health conditions from their respective homes. The outreach activity and the formation of Jumantik Bocah (JUMBO KLENGGOTAN) were successfully formed as many as 12 people, namely as many as @2 people from the area of RT 1, RT 2, RT 3, RT 5, RT 6, RT 8. Implementation of larva monitoring activities in RT 1-8 Klenggotan Hamlet, Srimulyo, Bantul, D. I Yogyakarta conducted by students has been carried out for three weeks as many as 40 house samples resulted in a larva free rate (ABJ) of 53.3%. This figure is still far from the quality standard according to PMK Number 50 of 2017, that the larvae free rate (ABJ) of Aedes aegypti and/or Aedes albopictus mosquito larvae is ≥95%.